Reproductive endocrine characteristics and in vitro fertilization treatment of female patients with partial 17α-hydroxylase deficiency: Two pedigree investigations and a literature review - Jiang, Shutian; Xu, Yue; Qiao, Jie; Wang, Yao; Kuang, Yanping (Frontiers in Endocrinology, 2022)
Background: 17α-hydroxylase/17, 20-lyase deficiency (17-OHD) is caused by the mutations of CYP17A1 gene. The classical phenotype of 17-OHD includes hypertension, hypokalemia, and abnormal sexual development, with partial 17-OHD typically less severe than the complete deficiency. Infertility is always one of the main clinical manifestations of partial 17-OHD. However, to date, the pregnancy potentials of partial 17-OHD females have rarely been investigated, and few live-birth cases have been reported. Besides, the reproductive endocrine characteristics of partial 17-OHD females have not been completely clarified and the treatment skills of in vitro fertilization and embryo transfer (IVF-ET) have not been well summarized yet. Methods: Two Chinese infertile females clinically diagnosed as partial 17-OHD were enrolled and their pedigree investigations were performed. Hormones were determined to depict the endocrine conditions of partial 17-OHD females. The adrenocorticotropic hormone (ACTH) stimulation test was performed to evaluate the functions of the adrenal cortex. Genotype analysis was conducted by next-generation sequencing (NGS) and Sanger sequencing was used to verify the results. IVF-ET was performed for the treatment of their infertility. Specifically, the progestin-primed ovarian stimulation (PPOS) protocol was chosen for controlled ovarian hyperstimulation (COH) cycles, and the hormone replacement treatment (HRT) protocol was adopted in frozen-thawed embryo transfer (FET) cycles. Results: Hormone assays revealed a reduced estradiol (E2) and testosterone (T) level, and an elevated progesterone (P4) level. The classic ACTH stimulating test evidenced a suboptimal response of cortisol to ACTH. Genotype analysis demonstrated that the proband1 carried two variants: c.1459_1467del (p.Asp487_Phe489del)het and c.995T>C (p.lle332Thr)het. The proband2 was a homozygote with the mutation of c.1358T>A (p.Phe453Ser)hom. The two female patients both succeeded in pregnancy and delivery of healthy babies through IVF-ET, with the usage of PPOS, HRT, and low-dose glucocorticoids. Conclusions: Partial 17-OHD female patients manifested menstrual cycle disorders and infertility clinically; displayed high P4, low E2 and T; showed sparse pubic hair in physical examinations; and revealed multiple ovarian cysts in ultrasonic visualization. Moreover, the pregnancy potentials of infertile partial 17-OHD women seemed to increase with the adoption of IVF-ET. Considering the sustained elevated P4 level, PPOS is a feasible protocol for them in COH.